Atrial Function after the Atrial Switch Operation for Transposition of the Great Arteries: Comparison with Arterial Switch and Normals by Cardiovascular Magnetic Resonance. (18th December 2015) - Franzoso, Francesca D.; Wohlmuth, Christoph; Greutmann, Matthias; Kellenberger, Christian J.; Oxenius, Angela; Voser, Eva M.; Valsangiacomo Buechel, Emanuela R.
Abstract: Objectives: The atria serve as reservoir, conduit, and active pump for ventricular filling. The performance of the atrial baffles after atrial switch repair for transposition of the great arteries may be abnormal and impact the function of the systemic right ventricle. We sought to assess atrial function in patients after atrial repair in comparison to patients after arterial switch repair (ASO) and to controls. Methods: Using magnetic resonance imaging, atrial volumes and functional parameters were measured in 17 patients after atrial switch repair, 9 patients after ASO and 10 healthy subjects. Results: After the atrial switch operation, the maximum volume of the pulmonary venous atrium was significantly enlarged, but not of the systemic venous atrium. In both patients groups, independently from the surgical technique used, the minimum atrial volumes were elevated, which resulted in a decreased total empting fraction compared with controls ( P < .01). The passive empting volume was diminished for right atrium, but elevated for left atrium after atrial switch and normal for left atrium after ASO; however, the passive empting fraction was diminished for both right atrium and left atrium after both operations ( P < .01). The active empting volume was the most affected parameter in both atria and both groups and active empting fractions were highly significantly reduced compared with controls. Conclusion: Atrial function is abnormal in all patients, after atrial switch and ASO repair. The cyclic volume changes, that is, atrial filling and empting, are reduced when compared with normal subjects. Thus, the atria have lost part of their capacity to convert continuous venous flow into a pulsatile ventricular filling. The function of the pulmonary venous atrium, acting as preload for the systemic right ventricle, after atrial switch is altered the most.